READING PROBLEMS IN VOCATIONAL HIGH SCHOOL - FITRI MAY DANTHI SARAGIH; NATALIA VERONIKA SITUMEANG; SITI TASYA JELITA MANURUNG; NOVITA SARI DEWI SINAGA; SELVIANA NAPITUPULU (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2022)
This study aims to find the difficulties when reading English which are mostly faced by students vocational students. This study used qualitative research methods. The research instrument is observations and interviews. Based on the results of observations and interviews, it was found that students find reading difficulties such as (1) not liking English lessons, (2) mental problems, (3) boring teacher teaching techniques (4) mistakes in word pronunciation. Reading skills are very important for us because by reading we will get the information we need easily. Therefore, it is necessary to conduct this research to solve these problems with reading difficulties experienced by students, so there are improvements for the future and students' reading skills will improve.